Brahms's Vocal Duets and Quartets with Piano : A Guide with Full Texts and Translations - Stark, Lucien, 1929-2012 (Book collections on Project MUSE., 1998)
In this sequel to A Guide to the Solo Songs of Johannes Brahms, Lucien Stark opens up a beautiful and largely neglected repertoire, providing the full German text for each song, along with a new English translation, notes on vocal ranges, and a wealth of engaging commentary of technical, aesthetic, and historical interest.